Implementation of Blended Learning During COVID-19 Pandemic on Civic Education Subjects in Millenial Generation Era - Feri Wagiono; Syahrial Shaddiq; Febi Junaidi (research, training and philanthropy institution Natural Aceh, 2022)
This article was written related to the Indonesian government's policies during the COVID-19 emergency, triggering innovation in learning. The complexity of implementing distance learning (PJJ) in the 4.0 era creates new problems, especially for the education of students in secondary schools. The learning process has changed drastically. Blended learning in education is not only face-to-face but also integrated online learning from home. The purpose of this article is to discuss the application of blended learning-based learning during the COVID-19 pandemic subject matter for Pancasila and Civic Education (PPKn) for millennial generations students of Junior High School Muhammadiyah 1 Kroya with character. This research is qualitative. The research subjects consisted of the principal, 2 PPKn teachers, and 46 grade 8 students of SMP Muhammadiyah 1 Kroya. Data collection techniques in the study used interview, documentation, and observation techniques. Data analysis techniques are reduction, collection, presentation of data, and conclusions. The implementation of blended learning during the COVID-19 pandemic at SMP Muhammadiyah 1 Kroya was carried out in several stages, namely presentation/planning, implementation, student discussion guidance, practice, elaboration, demonstration, and student evaluation related to PPKn